High-altitude ancestry protects against hypoxia-associated reductions in fetal growth. Issue 5 (28th February 2007) - Julian, Colleen Glyde; Vargas, Enrique; Armaza, J Fernando; Wilson, Megan J; Niermeyer, Susan; Moore, Lorna G
Abstract : Objective: The chronic hypoxia of high-altitude (⩾2500 m) residence has been shown to decrease birth weight in all populations studied to date. However, multigenerational high-altitude populations appear protected relative to newcomer groups. This study aimed to determine whether such protection exists independently of other factors known to influence fetal growth and whether admixed populations (ie, people having both high- and low-altitude ancestry) show an intermediate level of protection. Design: 3551 medical records from consecutive deliveries to Andean, European or Mestizo (ie, admixed) women at low, intermediate or high altitudes in Bolivia were evaluated for maternal characteristics influencing fetal growth as measured by birth weight and the frequency of small for gestational age births (SGA or ⩽10th percentile birth weight for gestational age and sex). Two-way analysis of variance and χ 2 tests were used to compare maternal and infant characteristics. The effects of ancestry or altitude on SGA and birth weight were assessed using logistic or linear regression models, respectively. Results: Altitude decreased birth weight and increased SGA in all ancestry groups. Andean infants weighed more and were less often SGA than Mestizo or European infants at high altitude (13%, 16% and 33% respectively, p<0.01). After accounting for the influences of maternal hypertensive complications of pregnancy, parity, body weight, and number of prenatal visits, European relative to Andean ancestry increased the frequency of SGA at high altitude nearly fivefold. Conclusions: Andean relative to European ancestry protects against altitude-associated reductions in fetal growth. The intermediate protection seen in the admixed (Mestizo) group is consistent with the influence of genetic or other Andean-specific protective characteristics.